Controle de robôs móveis por fusão de sinais de controle usando filtro de informação descentralizado - Freire, Eduardo Oliveira (2002)
This thesis proposes an alternative approach to deal with the problem of mobile robot navigation, which is called fusion of control signals. The proposed technique has presented good results when a robot has to execute relatively complex tasks, like it is shown in the experiments here presented. The technique is developed with basis on the decentralised information filter, whose equations are here derived from the equations of the decentralised Kalman filter and the information filter. Motion controllers available in the literature and others introduced here for the first time are used to produce the control signals that are fused using a decentralised information filter in order to produce the overall output signal to be sent to the actuators. A stability analysis of the proposed architecture is also addressed.